Total synthesis of pachastrissamine (jaspine B) enantiomers from D-glucose - Ramana, C. V.; Giri, Awadut G.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Synthesis of both enantiomers of pachastrissamine is described from a common chiral template. The stereoselective construction of the central tetrahydrofuran units was based on the pseudodesymmetrization of a pentodialdo-1,4-furanose derivative taking advantage of the latent symmetry present. (c) 2006 Published by Elsevier Ltd.
Keywords: 4-furanose; chiron approach; Ohira-Bestmann reaction; pachastrissamine/jaspine B; pentodialdo-1; ring isomerization

Two modes of O-H center dot center dot center dot O hydrogen bonding utilized in dimorphs of racemic 6-O-acryloyl-2-O-benzoyl-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
The title compound, C(17)H(16)O(8), yields conformational dimorphs [forms (I) and (II)] at room temperature, separately or concomitantly, depending on the solvent of crystallization. The yield of crystals of form (I) is always much more than that of crystals of form (II). The molecule has one donor -OH group that can make intermolecular O-H center dot center dot center dot O hydrogen bonds with one of the two acceptor C O groups, as well as with the hydroxyl O atom; interestingly, each of the options is utilized separately in the dimorphs. The crystal structure of form (I) contains one molecule in the asymmetric unit and is organized as a planar sheet of centrosymmetric dimers via O H center dot center dot center dot O hydrogen bonds involving the OH group and the carbonyl O atom of the acryloyl group. In the crystal structure of form (II), which contains two independent molecules in the asymmetric unit, two different O-H center dot center dot center dot O hydrogen bonds, viz. hydroxyl-hydroxyl and hydroxyl-carbonyl (benzoyl), connect the molecules in a layered arrangement. Another notable feature is the transformation of form (II) to form (I) via melt crystallization upon heating to 411 K. The higher yield of form (I) during crystallization and the thermal transition of form (II) to form (I) suggest that the association in form (I) is more highly favoured than that in form (II), which is valuable in understanding the priorities of molecular aggregation during nucleation of various polymorphs.

Target cum flexibility: an alkyne [2+2+2]-cyclotrimerization strategy for synthesis of trinem library - Ramana, C. V.; Dushing, Mangesh P.; Mohapatra, Sradhanjali; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron Letters, 2011)
A rapid access to the central 4,5,6-tricyclic core of 4,5,6-trinems has been achieved by employing the alkyne [2+2+2]-cyclotrimerization as the key and final reaction in the synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Topochemical click reaction: spontaneous self-stitching of a monosaccharide to linear oligomers through lattice-controlled azide-alkyne cycloaddition - Pathigoolla, Atchutarao; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2012)
Keywords: Click chemistry; green chemistry; polymerization; pseudosugars; topochemistry

Triazole-linked anthracenyl-appended calix[4]arene conjugate as receptor for Co(II): synthesis, spectroscopy, microscopy, and computational studies - Mummidivarapu, V. V. Sreenivasu; Hinge, Vijaya Kumar; Tabbasum, Khatija; Gonnade, Rajesh G.; Rao, Chebrolu P. (Journal of Organic Chemistry, 2013)
A new triazole-linked anthracenyl-appended calix[4]arene-1,3-diconjugate (L) has been synthesized and characterized, and its single crystal XRD structure has been established. Binding properties of L toward different biologically relevant metal ions have been studied by fluorescence and absorption spectroscopy in ethanol. L exhibits selective recognition of Co2+ and can detect down to a concentration of 55 ppb (0.92 mu M). The roles of the calix[4]arene platform as well as the preorganized binding core in L's selective recognition have been demonstrated by studying appropriate control molecules. The mode of binding of L with Co2+ has been modeled both by DFT and MD computational calculations. L and its Co2+ complex could be differentiated on the basis of the nanostructural features observed in AFM and TEM.

Terahertz spectroscopy and solid-state density functional theory calculations of cyanobenzaldehyde isomers - Dash, Jyotirmayee; Ray, Shaurnik; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin B.; Gonnade, Rajesh G.; Ambade, Ashootosh V.; Joshi, Kavita; Pesala, Bala (Journal of Physical Chemistry A, 2015)
Spectral signatures in the terahertz (THz) frequency region are mainly due to bulk vibrations of the molecules. These resonances are highly sensitive to the relative position of atoms in a molecule as well as the crystal packing arrangement. To understand the variation of THz resonances, THz spectra (2-10 THz) of three structural isomers: 2-, 3-, and 4-cyanobenzaldehyde have been studied. THz spectra obtained from Fourier transform infrared (FTIR) spectrometry of these isomers show that the resonances are distinctly different especially below 5 THz. For understanding the intermolecular interactions due to hydrogen bonds, four molecule cluster simulations of each of the isomers have been carried out using the B3LYP density functional with the 6-31G(d,p) basis set in Gaussian09 software and the compliance constants are obtained. However, to understand the exact reason behind the observed resonances, simulation of each isomer considering the full crystal structure is essential. The crystal structure of each isomer has been determined using X-ray diffraction (XRD) analysis for carrying out crystal structure simulations. Density functional theory (DFT) simulations using CRYSTAL14 software, utilizing the hybrid density functional B3LYP, have been carried out to understand the vibrational modes. The bond lengths and bond angles from the optimized structures are compared with the XRD results in terms of root-mean-square-deviation (RMSD) values. Very low RMSD values confirm the overall accuracy of the results. The simulations are able to predict most of the spectral features exhibited by the isomers. The results show that low frequency modes (<3 THz) are mediated through hydrogen bonds and are dominated by intermolecular vibrations.

Three-component coupling involving arynes, aromatic tertiary amines, and aldehydes via aryl-aryl amino group migration - Bhojgude, Sachin Suresh; Baviskar, Dnyaneshwar R.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2015)
The transition-Metal-free multicomponent coupling of arynes, aromatic tertiary amines, and aldehydes proceeding via the aryl to aryl amino group migration has been demonstrated. This protocol allows rapid access to ortho-functionalized tertiary amines in moderate to good yields. Moreover, activated ketones can also be used as the aldehyde Component in the present reaction. The similarity of the aryl-aryl tertiary amino group migration with the Smiles rearrangement is striking.

Total synthesis of isocladosporin and 3-epi-isocladosporin - Mohapatra, Debendra K.; Maity, Saurabh; Banoth, Shivalal; Gonnade, Rajesh G.; Yadav, J. S. (Tetrahedron Letters, 2016)
A convergent total synthesis of isocladosporin and 3-epi-isocladosporin is reported starting from commercially available homoallyl alcohol in 10 longest linear steps with 28% overall yield. The key steps involved in the synthesis are cross-metathesis, tandem isomerization followed by C-O and C-C bond formation reactions for the synthesis of trans-2,6-disubstituted dihydropyrans developed by us, acylation reaction and Luche reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylation reaction; Cross-metathesis; Iodocyclization; Isocladosporin 3-epi-Isodadosporin; Luche reduction

Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.

Three-dimensional metal-organic polymer of multivalent hexaphenylbenzene - Madhu, Suresh; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Metal-Organic Frameworks(MOFs) synthesized from ligands more than ten co-ordinating sites may offer material applications due to their structural architecture. Herein, a synthesis of metal-organic framework is reported from a ligand featuring 12-aryl carboxylic acid groups appended on a hexaphenylbenzene and s-block element potassium. The synthesized MOF was characterized by thermogravimetric analysis, infrared spectroscopy and X-diffraction studies. The X-ray crystal structure of MOF was shown to have a significant number of trapped and coordinated water molecules in its three-dimensional framework.

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Tuning of terahertz resonances of pyridyl benzamide derivatives by electronegative atom substitution - Dash, Jyotirmayee (Journal of Infrared, Millimeter, and Terahertz Waves, 2018)
N-(pyridin-2-yl) benzamide (Ph2AP)-based organic molecules with prominent terahertz (THz) signatures (less than 5 THz) have been synthesized. The THz resonances are tuned by substituting the most electronegative atom, fluorine, at ortho (2F-Ph2AP), meta (3F-Ph2AP), and para (4F-Ph2AP) positions in a Ph2AP molecule. Substitution of fluorine helps in varying the charge distribution of the atoms forming hydrogen bond and hence strength of the hydrogen bond is varied which helps in tuning the THz resonances. The tuning of lower THz resonances of 2F-Ph2AP, 3F-Ph2AP, and 4F-Ph2AP has been explained in terms of compliance constant (relaxed force constant). Four-molecule cluster simulations have been carried out using Gaussian09 software to calculate the compliance constant of the hydrogen bonds. Crystal structure simulations of the above molecules using CRYSTAL14 software have been carried out to understand the origin of THz resonances. It has been observed that THz resonances are shifted to higher frequencies with stronger hydrogen bonds. The study shows that 3F-Ph2AP and 4F-Ph2AP have higher hydrogen bond strength and hence the THz resonances originating due to stretching of intermolecular hydrogen bonds have been shifted to higher frequencies compared to 2F-Ph2AP. The methodology presented here will help in designing novel organic molecules by substituting various electronegative atoms in order to achieve prominent THz resonances.
Keywords: Compliance constant; Density functional theory; Ph2AP molecule; Terahertz spectroscopy

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

TiCl4-n-Bu3N-mediated cascade annulation of ketones with alpha-ketoesters: a facile synthesis of highly substituted fused gamma-alkylidene-butenolides - Palange, Megha N.; Gonnade, Rajesh G.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2019)
A facile protocol for the synthesis of highly substituted fused gamma-alkylidene butenolides using direct annulation of ketones with alpha-ketoesters, which proceeds through TiCl4-n-Bu3N mediated aldol addition followed by an intramolecular enol-lactonization/cyclization cascade, is reported. Diverse 6-5, 7-5 and 8-5 fused bicyclic gamma-ylidene butenolides and highly substituted monocyclic analogs related to biologically relevant natural products were prepared from readily accessible ketone and alpha-ketoester building blocks. The highly step-economic cascade nature, good substrate scope, easy access to complex products with good to excellent yields, gram-scalability, demonstration of synthetic utility, and unambiguous structural confirmation through X-ray crystallography analyses and analogy are the salient features of this work.

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Tailoring diradicaloid properties of expanded isophlorinoids with systematic core-modification - Ambhore, Madan D.; Shukla, Pragati; Gonnade, Rajesh G.; Anand, Venkataramanarao G. (Chemical Communications, 2022)
Herein, we describe the synthesis, structural diversity and diradicaloid characteristics of 38 pi core-modified aromatic expanded isophlorins with eight heterocyclic rings. The diradicaloid character of expanded isophlorinoid macrocycles was engineered by systematic structural modification. Depending on the nature of the link between the heteroatoms, they adopt planar and non-planar conformations. This large structural variation with a significant difference in the extent of aromaticity is correlated with the magnitude of their respective diradical character.

Thermally stable P-chiral supramolecular phosphines, their self-assembly and implication in Rh-catalyzed asymmetric hydrogenation - Chandanshive, Amol C.; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry-A European Journal, 2024)
P-chiral supramolecular phosphine ligands are crucial for asymmetric transformations, but their synthesis is tedious. We report a one-step synthesis of thermally stable P-chiral supramolecular phosphines and their performance in the asymmetric hydrogenation of functionalized alkenes. A rational designing and synthesis of (R, R)-QuinoxP* ligated palladium complex (Pd-2) in excellent yield is reported. This Pd-2 catalyzed a direct P-C coupling of 2,3-dihydro-1-H-phosphindole (A1)/1,2,3,4-tetrahydrophosphindoline (A2) with 1-(3-iodophenyl)urea (B1)/2-iodo /6-hydroxy pyridine (B2) and,produced corresponding ligands L1-L3. The P-C coupling between A1 and B2 produced 6-(2,3-dihydro-1H-phosphindol-1-yl)pyridine-2(1H)-one (L2) with an excellent enantiomeric excess of up to 99 %. L2 was found to be remarkably stable even at 150 degrees C and did not oxidize/hydrolyze for at least 24 hours in open air. Such thermal stability and an impediment to oxidation are unprecedented. L2 self-assembled and produced L2-C1 (Pt), L2-C2(Pd), and L2-C3(Rh) assemblies. The utility of the self-assembled P-chiral ligand was demonstrated in the Rh-catalyzed asymmetric hydrogenation (AH) of functionalized olefins. The L2-C3 catalyzed AH of functionalized alkenes and delivered chiral products with excellent enantioselectivity of >99 %. A small library of 16 substrates was subjected to AH using L2-C3 to produce chiral compounds with excellent conversion and ee.
Keywords: asymmetric hydrogenation; Asymmetric phosphination; P-chiral phosphine; Self-assembly; Supramolecular phosphine

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Transition metal complexes of Thiadiazole-Picolinic acid: Crystal structures, DFT insights and anticancer activity - Torambetov, Batirbay; Khojabaeva, Gulnaz; Bharty, M. K.; Gupta, Sushil K.; Kadirova, Shakhnoza; Pradeep, S.; Dastager, Syed G.; Gonnade, Rajesh G. (Journal of Molecular Structure, 2026)
Five novel transition metal complexes [Ni(H2aeth)2(Pic)2] (1), [Co(H2aeth)2(Pic)2] (2), [Ni(H2aeth)2(Pic)(HPic)] ClO4 (3), [Co(H2aeth)2(Pic)(HPic)]ClO4 (4) and [Zn(H2aeth)2 (Pic)(HPic)]ClO4 (5) were synthesized using a 2amino-5-ethylthio-1,3,4-thiadiazole (H2aeth) and picolinic acid (HPic) as co-ligands. These complexes were characterized by FT-IR, UV-Vis., X-ray photoelectron spectroscopy, TG-DTA, and single-crystal X-ray techniques. Crystallographic analysis confirmed distorted octahedral geometries around the metal centers with extensive hydrogen bonding networks promoting supramolecular assembly in the solid state. X-ray photoelectron spectroscopy (XPS), validated the +2 oxidation state of each metal center. Thermal studies indicated multistep decomposition processes resulting in the formation of metal oxides. Density functional theory (DFT) and timedependent DFT calculations were employed to explore electronic structures and predict UV-Vis. transitions, which showed good agreement with experimental data. Frontier molecular orbital (FMO) analysis revealed that Ni(II) complexes 1 and 3 are softer and more reactive, consistent with their observed biological activity. The anticancer potential of complexes 1-5 was evaluated in vitro using the MCF-7 human breast cancer cell line and the MTT assay. Complex 1 exhibited the strongest cytotoxicity (IC50 = 26.5 mu g/mL) followed by complexes 3 (34.9 mu g/mL), 4 (46.4 mu g/mL), 2 (81.1 mu g/mL), and 5 (103.3 mu g/mL). The observed activity trends correlate with metal identity and coordination environment, underlining the role of electronic and structural factors in modulating bioactivity. These findings suggest that thiadiazole-picolinate metal complexes, particularly those based on Ni (II), are promising scaffolds for anticancer drug development.
Keywords: Anti-cancer activity; crystal structure; DFT calculation; MCF-7 cell line; Picolinic acid; Thiadiazole complexes